Step
*
2
of Lemma
raise-left-endpoint-rless
1. ∀a:ℝ. ∀n:ℤ.  ((a + (r(n + 1) * a)) = (r(n + 2) * a))
⊢ ∀a,b:ℝ. ∀n:ℕ+.  ((a < b) 
⇒ ((a < raise-left-endpoint(a;b;n)) ∧ (raise-left-endpoint(a;b;n) < b)))
BY
{ (Auto
   THEN Unfold `raise-left-endpoint` 0
   THEN (RWO "int-rdiv-req" 0 THENA Auto)
   THEN (RWO "int-rmul-req" 0 THENA Auto)
   THEN nRMul ⌜r(n + 2)⌝ 0⋅) }
1
1. ∀a:ℝ. ∀n:ℤ.  ((a + (r(n + 1) * a)) = (r(n + 2) * a))
2. a : ℝ
3. b : ℝ
4. n : ℕ+
5. a < b
⊢ ((r(2) * a) + (r(n) * a)) < (a + b + (r(n) * a))
2
1. ∀a:ℝ. ∀n:ℤ.  ((a + (r(n + 1) * a)) = (r(n + 2) * a))
2. a : ℝ
3. b : ℝ
4. n : ℕ+
5. a < b
6. a < raise-left-endpoint(a;b;n)
⊢ (a + b + (r(n) * a)) < ((r(2) * b) + (r(n) * b))
Latex:
Latex:
1.  \mforall{}a:\mBbbR{}.  \mforall{}n:\mBbbZ{}.    ((a  +  (r(n  +  1)  *  a))  =  (r(n  +  2)  *  a))
\mvdash{}  \mforall{}a,b:\mBbbR{}.  \mforall{}n:\mBbbN{}\msupplus{}.    ((a  <  b)  {}\mRightarrow{}  ((a  <  raise-left-endpoint(a;b;n))  \mwedge{}  (raise-left-endpoint(a;b;n)  <  b)))
By
Latex:
(Auto
  THEN  Unfold  `raise-left-endpoint`  0
  THEN  (RWO  "int-rdiv-req"  0  THENA  Auto)
  THEN  (RWO  "int-rmul-req"  0  THENA  Auto)
  THEN  nRMul  \mkleeneopen{}r(n  +  2)\mkleeneclose{}  0\mcdot{})
Home
Index